Cultures of governance and peace : a comparison of EU and Indian theoretical and policy approaches - Richmond, Oliver P.; Burgess, J. Peter; Samāddāra, Raṇabīra (Manchester International Relations, 2016)
This volume brings together insights which look at the intersection of governance, culture and conflict resolution in India and the European Union.